1995
DOI: 10.1016/0005-2736(95)00117-l
|View full text |Cite
|
Sign up to set email alerts
|

Molecular order and dynamics of phosphatidylcholine bilayer membranes in the presence of cholesterol, ergosterol and lanosterol: a comparative study using 2H-, 13C- and 31P-NMR spectroscopy

Abstract: We report the results of a comparative study of the molecular order and dynamics of phosphatidylcholine (PC) bilayer membranes in the absence and presence of cholesterol, ergosterol and lanosterol, using deuterium (2H) nuclear magnetic resonance (NMR) of deuterated phospholipid molecules, in addition to solid state 13C and 31P-NMR. Using dimyristoylphosphatidylcholines (DMPCs) specifically labeled at positions 2', 3', 4', 6', 8', 10' and 12' of the sn-2 chain together with the perdeuterated 2-[2H27]DMPC deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

75
219
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(297 citation statements)
references
References 95 publications
75
219
3
Order By: Relevance
“…(i) In the presence of SM, replacement of cholesterol by ergosterol results in a membrane order that is as high as the order of membranes of the well characterized raft mixture SM/PC/cholesterol. This result confirms previous reports showing the property of ergosterol to have a condensing effect on glycerophospholipids (43)(44)(45)(46). (ii) Yeast PI increases the order of membranes containing IPC, irrespective of whether cholesterol or ergosterol is used as the sterol in these mixtures.…”
Section: Guvs From Yeast Total Lipid Extracts Showsupporting
confidence: 91%
See 2 more Smart Citations
“…(i) In the presence of SM, replacement of cholesterol by ergosterol results in a membrane order that is as high as the order of membranes of the well characterized raft mixture SM/PC/cholesterol. This result confirms previous reports showing the property of ergosterol to have a condensing effect on glycerophospholipids (43)(44)(45)(46). (ii) Yeast PI increases the order of membranes containing IPC, irrespective of whether cholesterol or ergosterol is used as the sterol in these mixtures.…”
Section: Guvs From Yeast Total Lipid Extracts Showsupporting
confidence: 91%
“…Ergosterol differs from cholesterol in additional double bonds in the B ring and the hydrocarbon side chain and an additional methylation at C24, the latter two making the side chain stiffer and bulkier, respectively (59). These structural attributes were proposed to restrict the motions of acyl chains more efficiently and thus lead to stronger ordering by ergosterol as compared with cholesterol (43)(44)(45)(46). As judged from the higher order of IPC/ergosterol membranes, this effect is more pronounced for IPC, whereas the sterol structure does not seem to be critical for the ordering of C18-SM-containing bilayers (Fig.…”
Section: Ipc-ergosterolmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of the thickness of DPPC or DMPC bilayers at t [ t m as an effect of cholesterol can be explained by the known ability of cholesterol to suppress trans-gauche isomerisation of saturated phosphatidylcholine chains in their fluid state (Korstanje et al 1990;Kusumi et al 1986;Marsh and Smith 1973;Miao et al 2002;Mouritsen and Zuckermann 2004;Schreier-Muccillo et al 1973;Urbina et al 1995;Vist and Davis 1990). Huang and Feigenson (1999) proposed the ''umbrella model'' as an explanation of this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that POPC and cholesterol exist at this concentration in an ordered lattice arrangement. Evidence that POPC and DPPC or DMPC interact differently with cholesterol and other sterols is also contained in studies of Urbina et al 12 They utilize NMR spectroscopy to comparatively study POPC, DPPC, and DMPC bilayers containing, separately, cholesterol, ergosterol, and lanosterol at sterol concentrations between 10% and 50%. They conclude that the sterols have a less marked effect on POPC than they have on DPPC.…”
Section: Introductionmentioning
confidence: 99%